Advances in Research on the Cardiovascular Complications of Acromegaly - Yang, Han; Tan, Huiwen; Huang, He; Li, Jianwei (Frontiers in Oncology, 2021)
Cardiovascular-related complications are one of the most common complications in patients with acromegaly, and can lead to an increased risk of death. Hypertension and cardiomyopathy are the main cardiovascular complications. The characteristics of acromegalic cardiomyopathy are concentric biventricular hypertrophy and diastolic dysfunction. In addition, arrhythmia and heart valve disease are common cardiac complications in acromegaly. Although the underlying pathophysiology has not been fully elucidated, the spontaneous overproduction of GH and IGF-1, increasing age, prolonged course of disease and the coexistence of other cardiovascular risk factors are crucial to cardiac complications in patients with acromegaly. Early diagnosis and appropriate treatment of acromegaly might be beneficial for the prevention of cardiomyopathy and premature death.